Design and Synthesis of Novel 6-(Substituted phenyl)-[1,3]dioxolo[4′,5′:4,5]benzo[1,2-d]thiazole Compounds as Tyrosinase Inhibitors: In Vitro and In Vivo Insights - Hyeon Seo Park; Hee Jin Jung; Hye Soo Park; Hye Jin Kim; Sang Gyun Noh; Yujin Park; Pusoon Chun; Hae Young Chung; Hyung Ryong Moon (Molecules)
The 2,4-dihydroxyphenyl group is commonly present in the chemical structures of potent tyrosinase inhibitors. Based on this observation, a series of 6-(substituted phenyl)-[1,3]dioxolo[4′,5′:4,5]benzo[1,2-d]thiazole compounds 1–13 were designed and synthesized as potential tyrosinase inhibitors. Among these, compounds 5 and 9 strongly inhibited mushroom tyrosinase activity. Particularly, compound 9 exhibited nanomolar IC50 values regardless of the substrate used, whereas kojic acid yielded IC50 values of 15.99–26.18 μM. Kinetic studies on mushroom tyrosinase revealed that compounds 5 and 9 competitively inhibited tyrosinase activity, findings further corroborated by in silico docking analysis. In B16F10 cell-based experiments, both compounds effectively inhibited the cellular tyrosinase activity and melanin formation. These inhibitory effects were confirmed through in situ cellular tyrosinase activity assays. Compound 9 exhibited strong antioxidant activity by scavenging radicals, suggesting that its ability to reduce melanin production may be attributed to a combination of its antioxidant and tyrosinase inhibitory properties. Additionally, five compounds, including compound 5, demonstrated effective depigmentation activity in vivo in zebrafish embryos, and their depigmentation efficacy was similar to that of kojic acid, even at concentrations hundreds of times lower. These findings suggest that 6-(substituted phenyl)-[1,3]dioxolo[4′,5′:4,5]benzo[1,2-d]thiazole compounds may be promising anti-melanogenic agents.